Cytoplasmic epigenetics: proteins acting as genes - Wickner, Reed (Henry Stewart Talks, 2007)
Prions (infectious proteins) include several self-propagating amyloids of S. cerevisiae and Podospora anserina and a self-activating enzyme of S. cerevisiae, these non-chromosomal genetic elements are genes composed of protein, just as nucleic acids can catalyse enzymatic reactions, the amyloid-based prions [PSI+] and [URE3] are diseases of yeast, but the [Het-s] prion of Podospora carries out a normal function for that organism, heterokaryon incompatibility
Archived at 2018/12/10